TEACHING GRAPHIC SYMBOLS IN PRIMARY AND SECONDARY SCHOOL TEXTBOOKS OF TURKISH LESSON - Kemalettin DENİZ and İsmail Yavuz ÖZTÜRK (International Journal of Eurasia Social Sciences, 2015)
This study intended to fix the situation of graphical symbols in Turkey’s public places in Turkish lesson that aims to educate individuals have effective communication skills. The Single Screening Model was used for this study. According to it, books were searched depending on the curriculums to understand whether the necessary teaching on this symbols was given within the lesson of Turkish. According to the analyses in this study, from the perspective of primary school and secondary school teaching activities, Turkish lesson’s curriculum has adequate gains about the teaching of graphical symbols in public places. However including Turkish lesson’s, there are no graphical symbols that can be used in public places adequately. Those which are given in these books are bounded by trafic signs. In the light of this investigation, solutions for teaching graphical symbols problems in Turkey was also given.